2001
DOI: 10.1080/00343400120058424
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics, Location and Regional Innovation: A Comparison Between Israeli and German Industrial Firms

Abstract: In recent years, a growing number of researchers have been anempting to gain a betcer understanding of the variation in the rate of spatial innovation of different industrial plants. Several of these studies have investigated the similarity and dissimilarity of spatial innovation between countries. This paper reports the results of a large study carried out jointly by a team of researchers from Germany and Israel In Germany, the study focused on Baden, the western part of the state of Badell-WUrttemberg; and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Quinn and Rohrbaugh (1983) model of organisational effectiveness was used as the basis for measuring performance. The validation of this approach is evident in its use in previous research (Miron et al, 2004;Brockman and Morgan, 2003;Frenkel et al, 2001;Walton and Dawson, 2001). Brockman and Morgan (2003) emphasise the importance of organisational learning as an important capability for achieving competitive advantage.…”
Section: Proposed Modelmentioning
confidence: 84%
See 1 more Smart Citation
“…Quinn and Rohrbaugh (1983) model of organisational effectiveness was used as the basis for measuring performance. The validation of this approach is evident in its use in previous research (Miron et al, 2004;Brockman and Morgan, 2003;Frenkel et al, 2001;Walton and Dawson, 2001). Brockman and Morgan (2003) emphasise the importance of organisational learning as an important capability for achieving competitive advantage.…”
Section: Proposed Modelmentioning
confidence: 84%
“…This classification groups industrial sectors according to direct and indirect R&D intensity and the ratio between R&D expenditure to value added, as defined by OECD/Eurostat (1997). Investment in innovation may be affected by type of sector, especially relative to low vs. high technology sectors, and reflected in R&D expenses (Acs and Audretsch, 1993;Frenkel et al, 2001). Comparing higher and lower technology sectors is relevant since industry structure impacts the company innovation behaviour (Shefe and Frenkel, 2005;Regev, 1998).…”
Section: Innovation Variablesmentioning
confidence: 99%
“…In that respect, we have developed a location choice model at a micro‐level having as a case study the Lyon urban area in France. While the majority of previous works address location choices of economic at a country (Frenkel, Shefer, Koschatzky, & Walter, ), region (Holl, ) or commune level (Manjón‐Antolín & Arauzo‐Carod, ), this work is considering an intraurban area as a spatial unit. Knowledge at such a detailed level of analysis can highlight the heterogeneities of location attributes emerging locally (Beaudry & Schiffauerova, ; Holl, ).…”
Section: Differences Between New and Relocating Establishments: Do Thmentioning
confidence: 99%
“…Several studies on innovation argue that firm size has been the key driver of R&D productivity (Cohen and Klepper ; Frenkel et al. ; Smith, Broberg, and Overgaard ). However, the literature on firm size and innovation has shown that no general pattern exists.…”
Section: Empirical Analysismentioning
confidence: 99%